Dualisme Pengaturan Pelanggaran Berat HAM dalam KUHP dan UU Pengadilan HAM Terhadap Prinsip Kepastian Hukum - Ely Dasnawati (Al-Azhar Islamic Law Review, 2024)
Law enforcement mechanisms related to violations of human rights have been regulated according to the provisions of Law No. 26 of 2000 concerning Human Rights Courts which specifically regulates serious violations of Human Rights. However, in 2023, there will be Law Number 1 of 2023 concerning the Criminal Code which has reformed the national criminal regulations which still adopt the laws inherited from the colonial Dutch East Indies. This of course raises a question, what is the position of the rules regarding the mechanism for resolving serious human rights violations regulated in the Human Rights Courts Law and the Criminal Code Law regarding the principle of legal certainty.This article aims to see how legal certainty is regarding serious violations of human rights in Law no. 1 of 2023 concerning the Criminal Code. The research method used is a qualitative research method with descriptive analytical research characteristics. This article presents arguments based on literature data to form conclusions. The research results have not achieved the principles of legal certainty in Law no. 1 of 2023 concerning the Criminal Code is due to the fact that there are different regulatory mechanisms for resolving serious violations of human rights with other laws that regulate the same substance. Mekanisme penegakan hukum terkait pelanggaraan hak asasi manusia telah diatur menurut ketentuan UU No 26 Tahun 2000 tentang pengadilan HAM yang secara spesifik mengatur mengenai pelanggaran berat HAM. Namun demikian di Tahun 2023, terdapat UU Nomor 1 Tahun 2023 tentang KUHP yang telah mereformasi aturan pidana nasional yang masih mengadopsi hukum peninggalan kolonial hindia belanda. Hal ini tentunya menimbulkan sebuah pertanyaan, bagaimana kedudukan aturan terkait mekanisme penyelesaian pelanggaran HAM berat yang diatur dalam UU Pengadilan HAM dengan UU KUHP terhadap prinsip kepastian hukum. Tulisan ini bertujuan untuk melihat bagaimana kepastian hukum terhadap pelanggaran berat hak asasi manusia dalam Undang-Undang No. 1 Tahun 2023 tentang KUHP. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan sifat penelitian deskriptif analisis tulisan ini memaparkan argumentasi berdasarkan data-data kepustakaan untuk menjadi kesimpulan. Hasil penelitian menunjukkan belum tercapainya prinsip-prinsip kepastian hukum dalam Undang-Undang No. 1 Tahun 2023 tentang KUHP disebabkan ada mekanisme pengaturan yang berbeda dalam penuntasan pelanggaran berat HAM dengan UU yang lain yang sama-sama mengatur subtansi yang sama.